2006
DOI: 10.1002/jor.20166
|View full text |Cite
|
Sign up to set email alerts
|

Nerve endings of the wrist joint: A preliminary report of the dorsal radiocarpal ligament

Abstract: As part of an investigation of the articular nerve ending populations in the wrist joint capsule associated with the anterior and posterior interosseous nerves, this study addresses the nerve ending population in the dorsal radiocarpal ligament. The ligaments were harvested from four wrists of two fresh cadavers within 12 h of death. Tissues were fixed, cryostat sectioned, and processed for fluorescence immunohistochemistry using antibody to protein gene product 9.5 (PGP 9.5), a general or pan neuronal marker,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 16 publications
2
22
0
Order By: Relevance
“…The latter topographic observation correlates to previous observations on general ligament histology and function, 6 as well as the findings in a recent publication on the distribution of mechanoreceptors in the human DRC. 7 The epifascicular region of ligaments previously has been referred to as the epiligamentous sheath, 8 denoting a structure surrounding, and not part of, a ligament. This area, however, has been proposed to be of importance for ligament nutrition and protection, as well as for providing support to the neurovascular bundles in the ligament.…”
Section: Discussionmentioning
confidence: 99%
“…The latter topographic observation correlates to previous observations on general ligament histology and function, 6 as well as the findings in a recent publication on the distribution of mechanoreceptors in the human DRC. 7 The epifascicular region of ligaments previously has been referred to as the epiligamentous sheath, 8 denoting a structure surrounding, and not part of, a ligament. This area, however, has been proposed to be of importance for ligament nutrition and protection, as well as for providing support to the neurovascular bundles in the ligament.…”
Section: Discussionmentioning
confidence: 99%
“…12 The roles of these nerve endings remain to be specified. However, our results suggest that these neural endings might have roles other than giving information about joint position.…”
Section: Discussionmentioning
confidence: 99%
“…3 The anatomic study of the wrist's innervation performed by Lin et al 12 showed that the AIN and PIN are responsible for the innervation of three-quarters of the wrist capsule. Therefore, the aim of this study was to determine whether sectioning the AIN and the PIN impairs kinesthesia.…”
mentioning
confidence: 99%
“…Although the PIN is classically thought of as being a "motor-only" nerve, the PIN also carries unmyelinated (group IV) afferent fibers from the wrist capsule as well as small myelinated (group IIA) afferent fibers from the muscles along its distribution. 73 Unmyelinated group IV fibers from muscles (designated as C-fibers when of cutaneous origin) have long been associated with nociception and pain. Whereas many group IV fibers respond to noxious stimuli, others have been shown to be excited by relatively innocuous mechanical stimuli.…”
Section: Managementmentioning
confidence: 99%